Adrenal Insufficiency as a Cause of Acute Liver Failure: A Case Report - Jamshid Vafaeimanesh; Mohammad Bagherzadeh; Mahmoud Parham (Case Reports in Endocrinology)
Introduction. Many diseases and conditions can contribute to elevated liver enzymes. Common causes include viral and autoimmune hepatitis, fatty liver, and bile duct diseases, but, in uncommon cases like liver involvement in endocrine disorders, liver failure is also seen. Adrenal insufficiency is the rarest endocrine disorder complicating the liver. In the previously reported cases of adrenal insufficiency, mild liver enzymes elevation was seen but we report a case with severe elevated liver enzymes and liver failure due to adrenal insufficiency. Based on our knowledge, this is the first report in this field. Case Report. A 39-year-old woman was referred to emergency ward due to drowsiness and severe fatigue. Her laboratory tests revealed prothrombin time: 21 sec, alanine aminotransferase (ALT): 2339 IU/L, aspartate aminotransferase (AST): 2002 IU/L, and ALP: 90 IU/L. No common cause of liver involvement was discovered, and eventually, with diagnosis of adrenal insufficiency and corticosteroid therapy, liver enzymes and function became normal. Finally, the patient was discharged with good general condition. Conclusion. With this report, we emphasize adrenal insufficiency (primary or secondary) as a reason of liver involvement in unexplainable cases and recommend that any increase in the liver enzymes, even liver failure, in these patients should be observed.